Pseudo-Contraband. Controversial Issues Regarding the Interpretation of the Smuggling Offense: Array - Dumitrache, Ana Alina Ionescu; Popa, Ioan Daniel (Journal of Danubian Studies and Research, 2020)
The article analyzes the notion of smuggling, as provided in art. 270 para. (3) of Law 86/2006, Romanian Customs Code, the conditions necessary for its legal existence, according to the legislation of the Romanian state in force, compared to the controversial interpretation of the illicit act of smuggling, as generating criminal liability for those correlative facts, provided and sanctioned under the same conditions as the crime of smuggling. On the interpretation of this notion, different opinions were expressed, among which, the opinion of accepting the notion of smuggling “lato sensu”, expressed also by Decision 32/2015 of the High Court of Cassation and Justice, the Panel for solving legal issues of criminal law and a second opinion, which belongs in particular to legal practitioners, according to which the notion of smuggling must be interpreted strictly in the form of the crime of smuggling. In this article, we will highlight a series of negative consequences that may arise from an extensive interpretation of the rule of law in the sense of broadening the initial content of the rule of law, in relation to its textual wording. We will also try to highlight the limits of the application of general legal norms in the field regulated by the special law, on the principle of “specialia generalibus derogant”, as well as the requirements necessary for the existence of criminal liability in case of assimilated facts. The study was carried out starting from practical aspects of the relevant national jurisprudence, of some concrete cases in which, the coherent and correct application of the legal norms applicable to each of the situations can generate, in our opinion, the reasonable suspicion of committing serious judicial errors, effects on the observance of fundamental human rights and freedoms, the achievement of the purpose of the law in correcting the unlawful conduct of the perpetrator and the subjection of the Romanian state to some unjustified and exaggerated expenses in relation to the seriousness of the facts brought to trial.